Revision of the genus Sinopalaeocossus Hong (Hemiptera: Palaeontinidae), with description of a new species from the Middle Jurassic of China - Wang, Bo; Zhang, Haichun C.; Fang, Yan; Duan, Ye (Zootaxa, 2006)
The diagnostic characters for Sinopalaeocossus Hong, 1983, belonging to the Palaeontinidae Handlirsch, 1906, are revised. This genus is remarkably different from others in the fore wing, whose branches of Sc are obscure and antenodal region is square; and in the hind wing, whose M 3+4 is unbranched and arises from stem M, whose M 1+2 fork is more distal and A 1 is absent. A new species, Sinopalaeocossus trinervus sp. nov., is described based on two well preserved specimens from the Middle Jurassic of Daohugou, Inner Mongolia, China; this is the first palaeontinid specimen with complete fore and hind wings articulated.